Intramolecular Fuzzy Interactions Involving Intrinsically Disordered Domains - Arbesú, Miguel; Iruela, Guillermo; Fuentes, Héctor; Teixeira, João M. C.; Pons, Miquel (Frontiers in Molecular Biosciences, 2018)
Structural disorder is an essential ingredient for function in many proteins and protein complexes. Fuzzy complexes describe the many instances where disorder is maintained as a critical element of protein interactions. In this minireview we discuss how intramolecular fuzzy interactions function in signaling complexes. Focussing on the Src family of kinases, we argue that the intrinsically disordered domains that are unique for each of the family members and display a clear fingerprint of long range interactions in Src, might have critical roles as functional sensor or effectors and mediate allosteric communication via fuzzy interactions.